Purification and Characterization of Broccoli (Brassica Oleracea Var. Italica) Myrosinase (?-Thioglucosidase Glucohydrolase) - Mahn-Osses, A; Angulo-Neuburg, A (American Chemical Society, 2014)
Myrosinase (?-thioglucosidase glucohydrolase, EC 3.2.1.147) from broccoli (Brassica oleracea var. italica) was purified by ammonium sulfate precipitation followed by concanavalin A affinity chromatography, with an intermediate dialysis step, resulting in 88% recovery and 1318-fold purification. These are the highest values reported for the purification of any myrosinase. The subunits of broccoli myrosinase have a molecular mass of 50-55 kDa. The native molecular mass of myrosinase was 157 kDa, and accordingly, it is composed of three subunits. The maximum activity was observed at 40 °C and at pH below 5.0. Kinetic assays demonstrated that broccoli myrosinase is subjected to substrate (sinigrin) inhibition. The Michaelis-Menten model, considering substrate inhibition, gave Vmax equal to 0.246 ?mol min-1, Km equal to 0.086 mM, and KI equal to 0.368 mM. This is the first study about purification and characterization of broccoli myrosinase. © 2014 American Chemical Society.